Sistem Pakar Kepemilikan Jaminan Kesehatan Untuk Peningkatan Kesehatan Masyarakat Dengan Metode Forward Chaining - Alhamidi, Alhamidi; iswandy, eka; Budiman, Arif; Hernando, Luki (Jurnal Sistem Informasi Dan Informatika, 2024)
An expert system is defined as a computer system that can approximate the decision-making logic of human experts. By using forward chaining inference logic for the consultation process, it is hoped that an expert system based on information technology can be built to determine the category of people who are classified as poor or not poor. Thus, the Forward Chaining Method can be implemented in tracking the ownership of health insurance cards in an effort to equalize the level of public health, so that this system can make it right on target and effective.